X-ray CT Analysis after Blast of Composite Sandwich Panels. (2016) - Rolfe, Emily; Kelly, Mark; Arora, Hari; Hooper, Paul A.; Dear, John P.
Abstract: Four composite sandwich panels with either single density or graded density foam cores and different face-sheet materials were subjected to full-scale underwater blast testing. The panels were subjected to 1kg PE4 charge at a stand-off distance of 1 m. The panel with graded density core and carbon fiber face-sheets had the lowest deflection. Post-blast damage assessment was carried out using X-ray CT scanning. The damage assessment revealed that there is a trade-off between reduced panel deflection and panel damage. This research has been performed as part of a program sponsored by the Office of Naval Research (ONR).